Co się stało z konfessyjonistą? Dzieje leksemu w polszczyźnie - Michalska-Górecka, Paulina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The history of the lexeme konfessyjonista shows that the word is a neologism that functioned in the literature of the sixteenth century in connection with religious documents/books, such as the Protestant confessions. Formally and semantically, it refers to Confessio Augustana, also to her Polish translations, and to the Konfesja sandomierska, as well as konfessyja as a kind of genre. In the Reformation and Counter-Reformation period, the word konfessyja was needed by the Protestants; the word konfessyjonista was derived from him by the Catholics for their needs. The lexeme had an offensive tone and referred to a confessional supporter as a supporter of the Reformation. Perhaps the oldest of his certifications comes from an anonymous text from 1561, the year in which two Polish translations of Augustana were announced. The demand for a konfessyjonista noun probably did not go beyond the 16th century, its notations come only from the 60s, 70s and 80s of this century.